Photonics and AI in Computational Oncology: Accelerating the Design of Next-Generation Cancer Therapies - Barack Ndenga (Publisher, 2025)
Oncology remains one of the most challenging frontiers in modern drug discovery, largely due to the intrinsic complexity of tumor biology, characterized by genetic heterogeneity, adaptive resistance mechanisms, and rapid mutational evolution. Traditional in silico drug design—although powerful—often fails to keep pace with the dynamic nature of cancer, leading to long development cycles and reduced clinical efficacy. This paper introduces a novel computational framework that merges photonic computation and artificial intelligence (AI) to enable personalized cancer therapy design at unprecedented speed and precision. Building on the previously developed Photonically-Assisted AI Drug Design Pipeline (PAI-DDP), this study adapts and extends the model to oncological pathways, allowing real-time molecular generation, structural optimization, and pharmacological validation. In this hybrid system, photonics serves as an ultra-fast computational accelerator capable of simulating complex molecular interactions at light speed, while AI algorithms act as predictive engines that learn oncogenic behaviors and optimize candidate drug molecules accordingly. Preliminary simulations demonstrate up to a 90% reduction in drug design timelines, significantly enhanced binding specificity, and improved molecular stability against oncogenic targets such as EGFR and KRAS. This approach represents a paradigm shift in precision oncology—moving from static drug design toward adaptive, real-time, patient-specific therapeutic development. By fusing light-speed computation with intelligent prediction, PAI-DDP-Onco lays the groundwork for a new generation of computational cancer pharmacology capable of outpacing tumor evolution.
This dataset and accompanying publication present the 21st scientific article by BarackEinstein97, introducing the oncological extension of the Photonically-Assisted AI Drug Design Pipeline (PAI-DDP). The framework integrates photonics and artificial intelligence to enable real-time, adaptive, and personalized drug design targeting oncogenic receptors such as EGFR and KRAS.